Penerimaan Gerakan Sosial Transnasional Ikhwanul Muslimin di Turki Pasca Arab Spring - Nabhan Aiqani (Jurnal ICMES, 2018)
This article discusses the acceptance of the Muslim Brotherhood (IM) movement in the middle of Turkish society after the Arab Spring. After the turmoil of the Arab Spring, this movement has been banned in various countries, ranging from Egypt, Syria, Jordan, to Saudi Arabia. On the contrary, IM continues to grow in Turkey. This article analyzes this phenomenon by using the concept of three categorization of the emergence of transnational social movements until they are accepted in a country, namely environmental change, cognitive change and relational change. Environmental change in Turkey shows that Turkey is currently controlled by the AKP Party and it begun to look at the strategic Middle East region. Cognitive change explains the IM appreciative attitude towards the current Turkish government. Relational change shows that IM, which faces restrictions many countries, needs to look for other political opportunities so that its movement continues to exist, so in this case of IM, it chooses Turkey. Relational change categorization found the connection between a social movement and the elite in government which can be explained by the concept of elite alliances, where social movements and the ruling government share interests on the basis of ideological similarities and views.